2000
DOI: 10.1007/s11663-000-0016-0
|View full text |Cite
|
Sign up to set email alerts
|

A model for prediction of pressure and redistribution of gas-forming elements in multicomponent casting alloys

Abstract: A finite element model for simulating macrosegregation in multicomponent alloys is extended to include the calculation of pressure and redistribution of gas-forming elements during solidification. The model solves the conservation equations of mass, momentum, energy, and alloy components, including gas-forming elements such as hydrogen and nitrogen. The results of transport calculations are contrasted with thermodynamic equilibrium conditions to establish the possible formation of pores, assuming that there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…However, a large number of trial experiments are time-consuming and money-consuming. Numerical simulation has offered an effective tool in prediction the thermal behavior and mass transport in direct laser deposition [11][12][13][14][15][16][17][18][19][20][21][22]. A three-dimensional mathematical model has been established in which the temperature field and flow field is obtained [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a large number of trial experiments are time-consuming and money-consuming. Numerical simulation has offered an effective tool in prediction the thermal behavior and mass transport in direct laser deposition [11][12][13][14][15][16][17][18][19][20][21][22]. A three-dimensional mathematical model has been established in which the temperature field and flow field is obtained [11].…”
Section: Introductionmentioning
confidence: 99%
“…The solute transfer and composition profiles evolution for binary system Fe-C during double-track direct metal deposition also have been reported [21]. Although the multicomponent mass transfer model has been built in metal casting and chemical engineering [22,23], such study for direct laser deposition has not been reported in the open peerreviewed literature.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation techniques, parametric or/and direct methods are usually apply to shape castings [26][27][28][29][30].…”
Section: Influence Of Cooling Rate On the γ′ Morphology And Size Distmentioning
confidence: 99%
“…When the volume fraction of liquid is one, the equations automatically become the Navier-Stokes and transport equations for an all-liquid region and when the volume fraction is zero, no fluid motion is possible and the system reduces to the energy equation. The model has already been presented in Reference [46], but the main features are repeated here for completeness. The following assumptions are used in the development of governing equations: The governing equations in dimensional form are: Continuity equation:…”
Section: Mathematical Model For Solidificationmentioning
confidence: 99%